1978
DOI: 10.1007/bf01891964
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury chloride induces learning deficits in prenatally treated Rats

Abstract: Methylmercury chloride (MMC) was given to pregnant rats on the 6th, 7th, 8th, and 9th day after conception in doses of 0.05 and 2.0 mg/kg/day. The female offspring of these animals were tested 90 days after birth for learning ability using operant conditioning procedures. The rats were kept at 90% of their normal body weight and trained in a lever-box to press a bar in order to obtain a food pellet. Significant differences in the acquisition speed became apparent when the ratio of bar presses to reward was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…They have a variety of effects on the central nervous system, resulting in a loss of coordination, behavioral disorders and learning deficits (Albers et al 1988;Musch et al 1978). Here, we focus on the actions of methyl mercury (MeHg) on voltage-activated ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…They have a variety of effects on the central nervous system, resulting in a loss of coordination, behavioral disorders and learning deficits (Albers et al 1988;Musch et al 1978). Here, we focus on the actions of methyl mercury (MeHg) on voltage-activated ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…At birth, the brain mercury levels of cohorts of the rats studied here were 0.5 or 9.1 ppm in the two exposure groups, placing them in the low to moderate range of exposure [4] although weaning these levels had dropped to 0.043 and 0.52 ppm, suggesting little mercury exposure during lactation. As adults, the rats were trained to respond under a Differential Reinforcement of High Rate (DRH) schedule of reinforcement, a procedure said to be sensitive to methylmercury [3,22] and behavior was followed until the rats were over 2 1/2 years old. Gross indicators of health, including growth and long-term survival of these rats and their cohorts were examined for comparison.…”
mentioning
confidence: 99%
“…Furthermore, nor mal hippocampal activity has been consi dered to be necessary for normal learning be havior [7], Behavioral studies from Spyker et al [16] and Spyker [17] of offspring from mcthylmercury-treated animals have shown a capability in the detection of subtle nervous system damage before any classical neurological symptoms appear, or when levels fall below those capable of inducing symptoms. Among the behaviorally abnormal offspring that re sulted from their exposure to methylmercury, Musch et al [12] have shown that these offspring definitely show a different learning capacity than matched controls. Hippocam pal lesions may be the underlying cause be hind these behavioral deviations.…”
Section: Discussionmentioning
confidence: 99%